EPIDEMIOLOGICAL ANALYSIS OF THE HUMAN IMMUNODEFICIENCY VIRUS - Nematova Nigora Urakovna; Matnazarova Gulbaxor Sultanovna; Mustanov Azamat Yunusovich; Abdukakharova Muattar Fakhridinovna; Xamaeva Nilufar Toshtemirovna; Bryanseva Elena Vlademirovna (Scholar Express Journals, 2023)
conduct an epidemiological analysis of the incidence of human immunodeficiency virus in the Republic of Uzbekistan and improve its prevention.
Keywords: HIV infection; analysis; morbidity; distribution